Kewenangan Pembatalan Peraturan Daerah Provinsi Oleh Menteri Dalam Negeri Dalam Hubungan Pusat Dan Daerah - Ricardo Marlon Mauwa; Salmon Eliazer Marthen Nirahua; Jemmy Jeffry Pietersz (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The Ministerial decree of Home Affairs (beleidsregels) in the Authority of Annulment provincial regulations is a form of modification of administrative law in preparing regional regulatory norms and has a hierarchical basis for the formation of provincial regulations.Purposes of the Research:  Reviewing and analyzing the suitability of legal norms instruments against the hierarchical laws and regulations within the authority to annulment provincial regulations by the Minister of Home Affairs, so that the instrument of authority in the context of central and regional relations should be a source of positive law based on the authority of state institutions (authority of the Minister of Home Affairs).Methods of the Research: This research is a case study using a normative juridical method with a case approach that is discussed descriptively, namely examining legal reasons (ratio decidendi) legitimacy and the basis for the authority of the Minister of Home Affairs in annulment Provincial Regulations and reviewing the authority of central relations and regions as indicators of government authority (Cq. Minister of Home Affairs) in the context to harmonize the implementation of public interest (administrative function = bestuurs function).Results of the Research: Modification of administrative law in practice of the authority to annulment provincial regional regulations by the Minister of Home Affairs in connection with central and regional relations in normative legal research on the laws and regulations applied in the Constitutional Court Decision No. Register: 137/PUU-XIII/2015; judicial review Article 251: (2),(3),(4),(8) and the Constitutional Court Decision No. Register: 56/PUU-XIV/2016; judicial review Article 251 : (1),(4),(5),(7), "as long as the phrase the authority to repeal provincial regional regulations by the Minister of Home Affairs is contrary to the 1945 Constitution and has no binding legal force". This creates confusion and dualism from the analogy principle by design : (1). Control of the administrative mechanism/ administrative function based on the normative formulation of Law Number 23 of 2014 the relevance of Permendagri Number 80 of 2015 (as the principal authority of the Minister of Home Affairs) is "a priore" in the practice of HTN is called as the authority of state institutions in an administrative appeal; and (2). Control of the juridical/judicial function mechanism, namely the legal authority to test according to the conception/hierarchy of laws and regulations based on the normative formulation of Law Number 12 of 2011 on the relevance of Presidential Regulation Number 87 of 2014 (which is the authority of the Supreme Court in the toetsingrehct/judicial mechanism review) is having the quality of “a posterore” on the other hand.